Resonant x-ray diffraction revealing chemical disorder in sputtered L10 FeNi on Si(0 0 1). (12th August 2016) - Frisk, Andreas; Lindgren, Bengt; Pappas, Spiridon D; Johansson, Erik; Andersson, Gabriella
Abstract: In the search for new rare earth free permanent magnetic materials, FeNi with a L10 structure is a possible candidate. We have synthesized the phase in the thin film form by sputtering onto HF-etched Si(0 0 1) substrates. Monatomic layers of Fe and Ni were alternately deposited on a Cu buffer layer, all of which grew epitaxially on the Si substrates. A good crystal structure and epitaxial relationship was confirmed by in-house x-ray diffraction (XRD). The chemical order, which to some part is the origin of an uniaxial magnetic anisotropy, was measured by resonant XRD. The 0 0 1 superlattice reflection was split in two symmetrically spaced peaks due to a composition modulation of the Fe and Ni layers. Furthermore the influence of roughness induced chemical anti-phase domains on the RXRD pattern is exemplified. A smaller than expected magnetic uniaxial anisotropy energy was obtained, which is partly due to the composition modulations, but the major reason is concluded to be the Cu buffer surface roughness.